2023
DOI: 10.2147/idr.s409708
|View full text |Cite
|
Sign up to set email alerts
|

A Candidemia Case Caused by a Novel Drug-Resistant Candida auris with the Y132F Mutation in Erg11 in Mainland China

Abstract: Background Candida auris is a pathogen first found in external ear canal, becoming a major threat to global health. Here, we describe a candidemia case caused by a novel drug-resistant Candida auris strain. Case Presentation An 80-year-old patient, with multiple serious medical conditions, was suffered from candidemia caused by Candida auris , died 9 days after admission in our hospital. Phylogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In this study, both isolates (28.6%, 2/7) from Hospital B belonged to Clade I. To date, only two isolates with Clade I have been reported in mainland China, both of which were from Beijing [ 15 , 24 ]. Similar to the strain of BJCA003 recently reported by Xu et al [ 24 ], both isolates with Clade I presented Y132F mutation in the ERG11 gene and resistance to amphotericin B ( Table 3 ).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In this study, both isolates (28.6%, 2/7) from Hospital B belonged to Clade I. To date, only two isolates with Clade I have been reported in mainland China, both of which were from Beijing [ 15 , 24 ]. Similar to the strain of BJCA003 recently reported by Xu et al [ 24 ], both isolates with Clade I presented Y132F mutation in the ERG11 gene and resistance to amphotericin B ( Table 3 ).…”
Section: Discussionmentioning
confidence: 60%
“…To date, only two isolates with Clade I have been reported in mainland China, both of which were from Beijing [ 15 , 24 ]. Similar to the strain of BJCA003 recently reported by Xu et al [ 24 ], both isolates with Clade I presented Y132F mutation in the ERG11 gene and resistance to amphotericin B ( Table 3 ). Phylogenetic analysis also showed that both isolates were closely related to the BJCA003 ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation